Faktor-Faktor Yang Berhubungan Dengan Tingkat Stres Orang Tua Pada Anakyang Di Rawat Di Ruangan Perinatologi - Sismi - Yeni; Riri - Novayelinda; Darwin - Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this studyis to determine the factorsthat related to parentalstress level of childrenbeing admitted in perinatology unit. In this study researcher used descriptive correlation design that was examine correlation of baby’s state of desease. type of treatment, parent’s age, educational level, sosial and economic status, parental knowledge of type caring the baby, family support system to parental stress level. The respondent of this research was 30 choosen by accidental sampling technique. The researcher used questionaire instruments that had been tested for validity and reliability. The result showed baby’s state of desease of treatment (p value= 0,001), sosial and economic (p value= 0,008), parental knowledge of type caring the baby (p value= 0,003), family support system (p value= 0,010) had a correlation with parental stress level. The factors that were not related to parental stress level were procedure of treatment (p value= 0,598), parent’s age (p value 0,330), and educational level (p value= 0, 307). This study suggests that the hospital should provide health education on stress management for parents who had children that being admitted in perinatology unit. Keywords: children, parents,stres Reference: 22 referensi (2001-2012)